Formação político-educativa do Movimento dos Trabalhadores Rurais Sem Terra (MST) no contexto do Governo Lula (2003 a 2010) - Coutinho, Célio Ribeiro (2014)
This work, the result of research conducted by the Movement of Landless Rural Workers (MST in Portuguese), was based on assumptions of Marx, Gramsci and Freire. The main objective consisted in studying the process of political-educational training of the MST, in its relationship with the Government Lula context (2003-2010). As theoretical and methodological apparatus, we opted for the use of the design of the dialectical method (analysis and synthesis); phenomenology (phenomenon description); content analysis (production of new meanings); content aggregation (associations analysis for categories and trends in the data); and grounded theory (theoretical scheme of production). In this type of qualitative research, we started with a case study in the design of participant and ethnographic research and used a quantitative instrumental. There were the option research techniques: categorical analysis of the thematic type (dismemberment of texts into categories and analog reunification); association analysis (identification of component analysis and categories); questioning technique (formulation of questions to examine the data); comparisons technique (identification and development of categories). Were adopted observation techniques and semi-structured interviews (63 interviews with internal and external members to MST). In the methodology yet were made use of tables, figures and mathematical formulas that facilitated the organization and analysis of empirical data. Among the findings of the survey stood out: the Descent and the MST Accommodation Pedagogy, phenomena that occurred simultaneously. The process of Descent was determined by the dependence of Government Policies and the Demobilization by Capital. The dependence resulting from the decrease of the Political and Organizational Power and the Institutionalization of the increase stemmed from the financial dependence and bureaucratization of the militancy work. Demobilization by Capital Disqualification determined by the Worker’s Party (Partido dos Trabalhadores – PT, in Portuguese) and demobilization by the government was based on the strength of capital, which dominated the state, the Lula’s government and the PT. The categorical composition of demobilization by Capital became more decisive of Descent than dependence on government policies. Based on the same determinations of Descent, identified the presence of Pedagogy Accommodation produced by MST Training Tying the Capital and Training for Conformation to government policies. This subordination resulting from the Training Compliance to Government Policies and Training Adaptation to Disqualification of the PT, resulted from the training environment for domination, provided by capitalist relations present in the state, the government and the PT. Originated Conformation of The Training Institutionalization and Training for Pacification was based on the bureaucratization of the work, financial dependence and decreased radical militancy. These factors result from the weakening of the role of organic intellectual of the MST. Part of militancy did resistance to the political strategy adopted which prevented the total loss of their political autonomy in government. Given the weakening of the Counter-Hegemonic MST fight, is presented as a suggestion to the Movement: a review of its policy strategy to deal with governments of the same political field and resumed the role in the struggle for land reform and for a socialist society.